Delayed Exercise is Ineffective at Reversing Aberrant Nociceptive Afferent Plasticity or Neuropathic Pain after Spinal Cord Injury in Rats - Detloff, Megan Ryan (Neurorehabil Neural Repair, 2015)
Neuropathic pain is a debilitating consequence of spinal cord injury (SCI) that correlates with sensory fiber sprouting. Recent data indicates that exercise initiated early after SCI prevents the development of allodynia and modulated nociceptive afferent plasticity. This study determined if delaying exercise intervention until pain is detected would similarly ameliorate established SCI-induced pain. Adult, female Sprague-Dawley rats with a C5 unilateral contusion were separated into SCI allodynic and SCI non-allodynic cohorts at 14 or 28 dpi when half of each group began exercising on automated running wheels. Allodynia, assessed by von Frey testing, was not ameliorated by exercise. Furthermore, rats that began exercise with no allodynia developed paw hypersensitivity within 2 weeks. At the initiation of exercise, the SCI Allodynia group displayed marked overlap of peptidergic and non-peptidergic nociceptive afferents in the C7 and L5 dorsal horn, while the SCI No Allodynia group had scant overlap. At the end of 5 weeks of exercise both the SCI Allodynia and SCI No Allodynia group had extensive overlap of the 2 c fiber types. Our findings show that exercise therapy initiated at early stages of allodynia is ineffective at attenuating neuropathic pain, but rather that it induces allodynia aberrant afferent plasticity in previously pain-free rats. These data, combined with our previous results suggest that there is a critical therapeutic window when exercise therapy may be effective at treating SCI-induced allodynia and that there are post-injury periods when exercise can be deleterious.